The Impact of Covid-19 Pandemic on Inflation in Indonesia - Dwi Rahmayani; Shanty Oktavilia; Phany Ineke Putri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
This study aims to analyze the existence and effect of Covid-19 on inflation in Indonesia. Covid-19, an outbreak of respiratory syndrome, has been named Corona Novel Virus 2019 or 2019-nCoV. The research method used Ordinary Least Squares (OLS) with inflation as a dependent variable. The interest rate, exchange rate, money supply, stock market, global and exported commodity price, and pandemic as independent variables. The pandemic indicator is measured by new cases added of Covid-19 per day in Indonesia. Using OLS, the result showed that the interest rate, stock market, exchange rate, and palm oil price have significantly affected Indonesia’s inflation. On the contrary, both raw oil, i.e., Brent oil price and pandemic, significantly negatively affect Indonesia’s inflation. However, the estimation fails to reflect the significant effect of the money supply to drive inflation. This paper implies that given higher new cases, Covid-19 per day has been the source of decreased inflation in Indonesia. It means that a pandemic is an impact on the weakness of the purchasing power of a consumer.